A Note on the effect of Inter Row Spacing, Plant Density and Nitrogen Application on Pearlmillet BJ-104 under Scanty Rainfall Conditions - Umrani, N K; Daftardar, S Y; Patil, C B; Walujkar, R B (Annals of Arid Zone, 2016)
- Â